(untitled) (The Pakistan Development Review, 2006)
There is a widespread impression among the Indian intelligentsia, foreign scholars, and residents of developed/rich countries that India’s economic growth has not reduced poverty, that globalisation has worsened poverty and/or income distribution, and that there are hundreds of millions of hungry people in India. These arguments are buttressed by recourse to India’s ranking on several social indicators. Esoteric debates about the comparability of survey data and gaps between NSS and NAS add to the confusion and allow ideologues to believe and assert whatever information suits the argument. What are the basic facts about poverty, income distributions, and hunger at an aggregate level? This paper reviews the available data and debates on this subject and comes to a commonsense view. It then tries to link some of the outcomes to the policy framework and programmes of the government. The paper finds that India’s poverty ratio of around 22 percent in 1999-2000 is in line with that observed in countries at similar levels of per capita income. The ratio is relatively high because India is a relatively poor/ low-income country, i.e., with low average income. 90 percent of the countries in the world have a higher per capita (average) income than India. The number of the poor is very high because India’s population is very large, the secondhighest in the world. India’s income distribution as measured by the Gini co-efficient is better than three-fourths of the countries of the world. The consumption share of the poorest 10 percent of the population is the sixth best in the world. Where India has failed as a nation is in improving its basic social indicators like literacy and mortality rates. Much of the failure is a legacy of the three decades of Indian socialism (till 1979-80). The rate of improvement of most indicators has accelerated during the market period (starting in 1980-81). The gap between its level and that of global benchmarks is still wide and its global ranking on most of these social parameters remains very poor. This is the result of government failure. The improvement in social indicators has not kept pace with economic growth and poverty decline, and this has led to increasing interstate disparities in growth and poverty. JEL classification: I3, I32, I38 Keywords: Hunger, Poverty, Public Goods, Public and Quasi-Public Goods and Services, Basic Education, Public Health, Sanitation